Non-penetrating Deep Sclerectomy and Phacoemulsification Performed in Two Stages in Patients with Glaucoma and Cataract - Francisco Rey García González; Dayamí Pérez Gómez; Rodolfo López Rodríguez; Patricia González Vargas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: surgical treatment of patients with primary chronic glaucoma and cataract remains a dilemma for ophthalmologists. Objective: to assess the postoperative results of non-penetrating deep sclerectomy with mitomycin C and phacoemulsification performed in two stages in patients with primary chronic glaucoma and cataract. Methods: a prospective descriptive study was conducted in 200 patients who underwent non -penetrating deep sclerectomy with mitomycin C and Nd:YAG laser peripheral iridotomy in the first stage and phacoemulsification with intraocular PMMA lens implantation in the second stage. Corrected visual acuity, intraocular pressure and filtering blebs, cup-to-disc ratio and intra -and postoperative complications were analyzed. Results: visual acuity improved from 0.4 before surgery to 0.7 a year after surgery. Sixty-two percent of the filtering blebs remained prominent and functional. After phacoemulsification, 17 % of the eyes continued under medication and 83% maintained the intraocular pressure below 17 mmHg, without treatment. Postoperative complications included moderate iridocyclitis (74 %) and posterior capsular opacity after a year (46%). Eighteen eyes (9 %) developed mild and transient endothelial decompensation. Conclusions: non -penetrating deep sclerectomy with mitomycin C and phacoemulsification performed in two stages lead to the surgical management of primary chronic glaucoma and good vision.